Lessons learned from COVID-19 impact of pandemic on children with neurological disorders in Sfax, Tunisia - Salma Zouari Mallouli; Sahar Najjar; Fatma Kamoun Feki; Olfa Jallouli; Sihem Ben Nsir; Wafa Bouchaala; Matilde Leonardi; Chahnez Charfi Triki (Intelektual Pustaka Media Utama, 2023)
To record the experience of caregivers for neurologically impaired children during the lockdown periods. Data from 286 children's caregivers were collected through an administered questionnaire to record: access to care services during the lockdown periods, causes underlying loss of access to care, mitigations adopted by caregivers and patients’ outcomes. The mean age of children was 8.11 years-old and sex ratio (F/M) was 0.66. They were mainly followed-up for epilepsy or epileptic encephalopathy (53%) and cerebral palsy (21%). During the lockdown periods, caregivers reported that 45% of children had no access to healthcare majorly for neurorehabilitation (76.7%) and medicines (70.7%). Most caregivers (36%) related limitations in access to fear from catching the virus. The majority resorted to continuation of the same treatment via primary healthcare facilities (41%) and postponement of their appointments (24%). Our results show that access to healthcare for children with neurological disorders was deeply disrupted during the COVID-19 pandemic. The already precarious health systems’ infrastructures might have been the main causes for this and should be thus considered in the health policy and planing.